2017
DOI: 10.1515/biol-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

The production of arabitol by a novel plant yeast isolate Candida parapsilosis 27RL-4

Abstract: Polyalcohol arabitol can be used in the food and pharmaceutical industries as a natural sweetener, a dental caries reducer, and texturing agent. Environmental samples were screened to isolate effective yeast producers of arabitol. The most promising isolate 27RL-4, obtained from raspberry leaves, was identified genetically and biochemically as Candida parapsilosis. It secreted 10.42– 10.72 g l-1 of product from 20 g l-1 of L-arabinose with a yield of 0.51 - 0.53 g g-1 at 28°C and a rotational speed of 150 rpm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…) was obtained 360 h after inoculation. Arabitol production achieved compares favorably with most of the literature reports presented in the literature concerning Ara production by yeasts (Kordowska‐Wiater et al ; Kordowska‐Wiater et al ; Koganti et al ; Koganti and Ju ; Kumdam et al ; Kordowska‐Wiater ).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…) was obtained 360 h after inoculation. Arabitol production achieved compares favorably with most of the literature reports presented in the literature concerning Ara production by yeasts (Kordowska‐Wiater et al ; Kordowska‐Wiater et al ; Koganti et al ; Koganti and Ju ; Kumdam et al ; Kordowska‐Wiater ).…”
Section: Resultssupporting
confidence: 74%
“…Kordowska‐Wiater et al () reported that among several strains of yeasts able to produce Ara from l ‐ arabinose, a C. parapsilosis strain was the most efficient one, giving 10–14 g l −1 of Ara from 20 g l −1 of L ‐arabinose, whereas effective were also the strains C. shehatae ATCC 22984 and Pichia guilliermondii DSM 70052, which secreted up to 9 g l −1 of Ara. Another newly isolated C. parapsilosis strain (27RL‐4), was revealed capable to produce up to 12 g l −1 of Ara with conversion yield 0·45–0·55 when trials were done in shake flasks (Kordowska‐Wiater et al ). One of the highest Ara concentrations ever indicated was by C. succiphila Y‐11998 which produced c. 81 g l −1 of Ara from arabinose during growth in shake flasks (Dien et al ).…”
Section: Discussionmentioning
confidence: 99%
“…All the adapted M. caribbica strains produced a significant amount of L-arabitol (20-22.2 g/L) during growth on L-arabinose, with M. caribbica D28L3 producing the most (22.2 g/L) with a yield of 0.783 g/g (Table 4). Kordowska-Wiater et al [46] isolated L-arabitol producing yeasts from raspberry. One of their isolates, C. parapsilosis 27RL-4, produced 10.72 g/L L-arabitol with a yield of 0.53 g/g.…”
Section: Discussionmentioning
confidence: 99%